(untitled) (Czech Journal of International Relations, 1967)
In the recent history of Europe, after the French Revolution, three major attempts were made to organize Europe based on the decisions of the leaders of the powers. Immediately after the Napoleonic wolves, the Congress of Vienna tried not only to determine the borders between the various European countries, but also to create a permanent organization of the great powers or their leaders and ruling circle. After all, there was a holy alliance for almost two generations determined by the force of international relations and only revolution in 1848 she shook off this factor with final effect and started a new era development of the European continent. At the Berlin Congress in the seventies of the last century, it stood in above all, the question of the new organization of other and south-eastern Europe, which showed urgency after the collapse of Turkey’s decisive influence and the emergence of the Italy at night. Also at this congress, an agreement was reached that the rulers circles of European powers decided the fate of this part of Europe.